The Impact of New Media on Tourism: A Study on West Bengal - Banerjee, Sraya; Sadhukhan, Priyanka (International Journal of Humanities and Education Development (IJHED), 2023)
This research report consists of informative data on tourism and the approach of new media in the tourism industry. The adaptation to new changes towards technology is a dynamic change. In this research proposal, there is a brief discussion on West Bengal tourism and some of the offbeat places in North Bengal. In the tourism industry, social media plays a significant role in communicating with tourists and guides. This research paper talks about tourism in West Bengal. This research paper initiated to discuss all the repercussions and growths of social media referred to tourism. Therefore, the role of social media platforms has a great impact on the tourism industry.